A study on status of anaemia in pregnant women attending urban health training centre, RIMS, Ranchi - Kumar, Vijay; Sunderam, Shalini; Haider, Shamim; Kashyap, Vivek (Indian Journal of Community Health, 2014)
Background: Anaemia in pregnant women has been regarded as very dangerous as it causes many maternal, fetal and neonatal complications. Fetal growth and pregnancy outcome largely depend upon the status of anaemia in pregnant women. Anaemia affects pregnant women all over the world - 52% in developing countries compared with 23% in the developed world. The difference in prevalence of anaemia in different parts of India including Jharkhand can be attributed to the different factors. A knowledge of these factors associated with anemia will help to formulate multipronged strategies to curtail this important public health problem in pregnancy. Aims & Objectives: (1) To know the socio-demographic profile of pregnant women attending Urban Health and Training Centre (UHTC), RIMS, Ranchi. (2) To know the status of anaemia among those pregnant women and its association with different factors. Material & Methods: A descriptive cross-sectional study done at ANC clinic of UHTC, RIMS, Ranchi to determine the status of anaemia in pregnant women and various socio-demographic factors associated with it. Hemoglobin level of 149 pregnant women selected by consecutive sampling was estimated by Cyanmethemoglobin method. Statistical Analysis: Template generated in MS excel sheet and analysis was done on SPSS software. Result: Out of total 149 pregnant women anaemia was found to be present in 99 (66.4%) women. A statistically significant association of anaemia (p<.05) was found with parity and birth interval from last birth. But the association of anaemia with ethnicity, education and other factors like gestational age (trimester) was not found to be statistically significant (p>.05). Conclusion: Occurrence of anaemia was much higher in this area as compared to national average. It indicates that the anaemia continues to be a major public health problem. Efforts should be geared towards the early detection and treatment of anaemia before delivery.